Efficacy and safety of high-dose thromboprophylaxis in morbidly obese inpatients - Wang, Tzu-Fei; Milligan, Paul E.; Wong, Catherine A.; Deal, Eli N.; Thoelke, Mark S.; Gage, Brian F. (Thrombosis and Haemostasis, 2014)
Obesity increases the risk for venous thromboembolism (VTE), but whether high-dose thromboprophylaxis is safe and effective in morbidly obese inpatients is unknown. It was the objective of this study to quantify the efficacy and safety of high-dose thromboprophylaxis with heparin or enoxaparin in inpatients with weight > 100 kilograms (kg) within the BJC HealthCare system. In a retrospective cohort study, we analysed 9,241 inpatients with weight < 100 kg discharged from three hospitals in the BJC HealthCare system from 2010 through 2012. We compared the incidence of VTE in patients who received high-dose thromboprophylaxis (heparin 7,500 units three times daily or enoxaparin 40 mg twice daily) to those who received standard doses (heparin 5,000 units two or three times daily or enoxaparin 40 mg once daily). The primary efficacy outcome was hospital-acquired VTE identified by International Classification of Diseases (ICD)-9 diagnosis codes. The primary safety outcome was bleeding events identified by ICD-9 codes. Among the 3,928 morbidly obese inpatients (weight > 100 kg and body mass index [BMI] ≥ 40 kg/m2), high-dose thromboprophylaxis approximately halved the odds of symptomatic VTE (odds ratio [OR] 0.52, 95% confidence interval [CI] 0.27–1.00; p = 0.050). The rate of VTE was 1.48% (35/2,369) in these morbidly obese inpatients who received standard doses of thromboprophylaxis, compared to 0.77% (12/1,559) in those who received high doses. High-dose thromboprophylaxis did not increase bleeding (OR 0.84, 95% CI 0.66–1.07, p = 0.15). Independent predictors of VTE were surgery, male sex, cancer, and BMI. In conclusion, high-dose thromboprophylaxis nearly halves the rate of VTE in morbidly obese inpatients.
Keywords: Obesity; obese inpatient; thromboprophylaxis; venous thromboembolism